Cluster Approach in the Implementation of the National Project “Health” in the Region - Y. N. Lapygin; E. A. Kovalev (Управленческое консультирование)
The practice of implementing the national project “Healthcare” at the regional level indicates a lag in the set rates, which causes the need to adjust the organizational structure of the healthcare system of the constituent entities of the Russian Federation. At the same time, the implementation of the recommendations of the Ministry of Health of the Russian Federation regarding the formation of a network of medical organizations of primary health care in combination with the recommendations of the Ministry of Health on the creation of centers for organizing primary health care in the regions creates the preconditions for building regional clusters in the field of healthcare in the constituent entities of the Russian Federation.The purpose of this study is to find ways to eliminate the lag of the regions of the Central Federal District of the Russian Federation in terms of achieving the goals set by the President of the country in the implementation of the national project “Healthcare”, focusing on the possibility of building a cluster policy in the process of developing a strategy for the development of modern Russian regions.The research methods are based on a systematic approach to the construction of regional clusters and the analysis of documents that make it possible to perform both statistical and content analysis, as well as methods that have found application in the development of strategically significant decisions, which include the classical analysis of external and internal environment factors, and the construction method. morphological matrices, and the Foresight method when focusing on the national development goals of the country by 2030, as well as design and programming methods typical for the strategic management of socio-economic systems.The results of the study are to develop an approach to resolve the accumulated problems that hinder the achievement of the set national development goals of the country until 2024 and until 2030, based on the formation of the cluster policy of the region in the health sector, implemented by the methods of strategic management of socio-economic systems, with the subsequent adjustment of the regional development strategy and the subsequent formation of the cluster policy of the region as a whole.The conclusions of the study are that the implementation of a sequence of procedures aimed at building a cluster focused on the implementation of the national project “Health” will allow the regions to preserve the population, as well as the health and well-being of people.